Comparative study of antigen-antibody interactionin the presence of cluster compounds of rhenium and cisplatin - М. V. Gorila; N. I. Shtemenko (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2005)
Two xenobiotics (rhenium cluster compound with adamantan and cisplatin) influences were investigated on the antigen–antibody reactions with immunodiffusion methods. The different characters of influences were shown.